Comparing Castability of Nickel-Chromium, Cobalt-Chromium, and Non-Precious Gold Color Alloys, Using two Different Casting Techniques - Elham Ansarifard; Mitra Farzin; Arghavan Zohour Parlack; Masumeh Taghva; Razieh Zare (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The castability of nonprecious gold color alloy using torch/ centrifugal and induction/vacuum-pressure casting techniques has not been studied yet. Purpose: This study was conducted to compare the castability of nickel chromium, cobalt-chromium and nonprecious gold color alloy using torch/centrifugal and induction/ vacuum-pressure casting techniques. Materials and Method: In this in vitro study, a total number of 54 identical acrylic wax meshes were prepared and divided into 6 different groups of 9 each. Group 1: nickel-chromium alloy, which was casted with induction technique. Group 2: nickel-chromium alloy was casted with centrifugal technique. Group 3: cobalt-chromium alloy was casted with induction technique. Group 4: cobalt-chromium alloy was casted with centrifugal technique. Group 5: nonprecious gold color alloy was casted with induction technique. Group 6: nonprecious gold color alloy was casted with centrifugal technique. Then castability of specimens was measured using modiﬁed Whitlock's method. The results were analyzed using two way ANOVA and post hoc tests. Results: ANOVA test revealed no statistically significant difference between different alloys with a p Value of 0.313. Moreover, it represented no significant differences within the groups regarding alloy types and casting techniques with a p Value of 0.511 and 0.682, respectively. Conclusion: No significant difference was found in the castability value of nickel-chromium, cobalt-chromium, and nonprecious gold color alloys. In addition, the castability value of three alloys tested in this study was not different by using torch/centrifugal or induction/vacuum-pressure casting machines.